Strategi Rancangan Pemasaran Penjualan Produk Vape Dengan Menggunakan Metode SWOT Dan QSPM - Sulaiman Alwi (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This thesis research is motivated by business competition in the e-cigarette (vape) industry. To face competition in the e-cigarette industry, the Trust Vape store must plan the right strategy to create opportunities for the products they sell. The purpose of this research is to find out why consumers buy vape products at the Trust Vape store, how the Trust Vape store can anticipate existing threats, how the Trust Vape store can compete with its competitors in the vape industry, and how the Trust Vape store can anticipate their weaknesses. In conducting this research, the author obtained data using observation, questionnaires, and interviews. Data analysis techniques used the SWOT and QSPM methods. The results of the research and discussions during the research process showed that the Trust Vape store can use its reputation in providing after-sales assistance to customers to avoid the threat of other stores deliberately lowering prices as an attraction for the store.